Improving the Stability and Performance of N-Type Organic Thin-Film Transistors - Brixi, Samantha (Université d'Ottawa / University of Ottawa, 2024)
Organic electronics are electronic devices which contain an organic semiconductor (OSC) rather than a typical inorganic based semiconductor. Organic electronics have the potential to usher in a new generation of flexible, light-weight, and wearable electronic devices; whether it is ultra-thin high-quality images from organic light-emitting diode displays, or highly sensitive point-of-care sensors and wearable health-monitoring systems, organic electronics represent a new horizon of technological development. Behind all these emerging applications, high performance organic thin-film transistors (OTFTs) are required. OSCs for electron-transporting (n-type) OTFTs has lagged behind their hole-transporting (p-type) counterparts for many years in terms of both performance and stability. While research in n-type OTFT materials has been increasing in the past decade, these hurdles persist. This thesis aims to address both the lower stability and performance of n-type OTFTs. Chapter 2 outlines a study that benchmarks the stability of various n-type OSCs, which can be used as a methodology for future studies. In Chapter 3, a study is presented that makes a first attempt to screen various chemical functionalities for OTFT performance stabilization. This chapter addresses a lack of organized approaches to the development of additives for organic electronic devices and highlights trends in potential chemical moieties to be used for improving device stability and performance. Particularly, pyridine was found to be a candidate material for enhancement of device stability. Chapter 4 directly applies the findings from Chapter 3, where poly(2-vinyl pyridine) (P2VP) was synthesized knowing the pyridine moiety had previously enhanced n-type OTFT stability. A variety of blend ratios with P2VP and our n-type OSC were studied, and the film properties examined to determine the optimal ratio for device stabilization. Finally, in Chapter 5 a study is presented incorporating not only an organic semiconducting layer, but also an organic poly(ionic liquid) gating layer. This represents a step towards fully-organic and less rigid device structures compared to previous studies. In this study, significant improvements in the OTFT operating voltages were found compared to previously fabricated devices, which would be feasible for real-world applications of these devices. All works beyond Chapter 2 have also used large numbers of replicate devices to address another issue endemic in the field: poorly represented statistics and few reported devices. This thesis represents contributions to methodologies for studying OTFT stability, the development of practical and low-cost additives for n-type OTFT stability, and the fabrication of majority organic and low-voltage operation OTFTs.
Keywords: OTFT; Organic Electronics; N-Type; Polymer; Stability